Regional Efficiency Analysis of an International Logistics Company: A Case Study - Ersoy, Pervin (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This study, conducted in collaboration with a US-based multinational logistics company, investigates the operational efficiency of cargo transportation firms in managing package collection and distribution. The primary objective is to identify areas for enhancing effectiveness. The research encompasses key variables such as delivered packages, pickups, truck numbers, couriers, delivery and pickup stops, total costs, daily delivery and pickup compensation. The study's focus centers on analyzing the operations of an international logistics firm in Izmir, Turkey, using the Data Envelopment Analysis (DEA) method which helps identify regions effectively managing processes. The frontier analyst program assessed the company's operations across 19 Izmir regions, leading to recommendations based on efficient regions. The research aims to provide a comprehensive roadmap for similar Third-Party Logistics Service Providers (3PLs) seeking to optimize cargo pickup operations. By adopting the study's suggested strategies and best practices, other 3PLs can enhance their package collection management and overall operational efficiency. In conclusion, the study underscores the value of employing the DEA method for evaluating cargo transportation operational efficiency, offering insights for improvement. The specific recommendations derived from efficient regions in Izmir serve as a guideline for logistics service providers looking to optimize package collection and distribution activities. Key words: Cargo Companies, 3PL, Data Envelopment Analysis (DEA), Efficiency, Logistics, Performance JEL Code: L91; L87; L10; L25